Proceedings of the 2019 Conference of the North 2019
DOI: 10.18653/v1/n19-1229
|View full text |Cite
|
Sign up to set email alerts
|

Simple Attention-Based Representation Learning for Ranking Short Social Media Posts

Abstract: This paper explores the problem of ranking short social media posts with respect to user queries using neural networks. Instead of starting with a complex architecture, we proceed from the bottom up and examine the effectiveness of a simple, word-level Siamese architecture augmented with attention-based mechanisms for capturing semantic "soft" matches between query and post tokens. Extensive experiments on datasets from the TREC Microblog Tracks show that our simple models not only achieve better effectiveness… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Attention mechanisms have become an integral part of compelling sequence modeling and transduction models in various tasks [9]. Evidence of NLP community moving towards attention-based models can be found by more attention-based neural networks developed by companies like Amazon [8], Facebook [16], and Salesforce [2]. The novel approach of Transformer is the first model to eliminate recurrence completely with self-attention to handle the dependencies between input and output.…”
Section: Related Workmentioning
confidence: 99%
“…Attention mechanisms have become an integral part of compelling sequence modeling and transduction models in various tasks [9]. Evidence of NLP community moving towards attention-based models can be found by more attention-based neural networks developed by companies like Amazon [8], Facebook [16], and Salesforce [2]. The novel approach of Transformer is the first model to eliminate recurrence completely with self-attention to handle the dependencies between input and output.…”
Section: Related Workmentioning
confidence: 99%
“…In contrast, MP-HCNN was explicitly designed with characteristics of tweets in mind: it significantly outperforms previous neural ranking models (see original paper for comparisons, not repeated here). We also copied results from Shi et al (2018), who reported even higher effectiveness than MP-HCNN.…”
Section: Searching Social Media Postsmentioning
confidence: 99%
“…The first two blocks of the table are copied from Rao et al (2019), who compared bag-of-words baselines (QL and RM3) to several popular neural ranking models as well as MP-HCNN, the model they introduced. The results of Rao et al (2019) were further improved in Shi et al (2018); in all cases, the neural models include interpolation with the original document scores. We see that Birch yields a large jump in effectiveness across all Microblog collections.…”
Section: Trec 2011-2014 Microblog Tracksmentioning
confidence: 99%